Bacteriological evaluation, antibiogram, and phenotypic detection of MBL-producing gram-negative bacteria isolated from outdoor patients with otorrhea attending Ayub medical Complex - Najeeb B.; Shakeela Q.; Qureshi S.A. (Kuwait Journal of Science)
Otitis media is frequently prevalent in developing countries and is primarily caused by bacteria. The current study aimed to study the patients to assess the occurrence rate, susceptibility pattern, and prevalence rate of metallo beta-lactamase (MBL) producing gram-negative bacteria to prevent the prevalent strains and direct the physicians to appropriate antibiotic therapy. The research study was conducted over nine-months, from November 2020 to July 2021, in which a total of 110 samples were collected from the outdoor-patients’ ear, nose, and throat (ENT) wards using sterile swabs and inoculated immediately on suitable culture media. The isolates were identified via conventional biochemical tests, and the susceptibility pattern of each isolate was tested using the Kirby-Bauer disc diffusion method. Out of the 110 total samples, merely 88.18% (97/110) ear samples were detected positive for the various strains of bacteria both in male and female patients with a mean age of 18.21 ± 15.86, contributing 54.64% and 45.36%, respectively. The most prevalent bacterial strain was Staphylococcus aureus (49.48%), followed by Pseudomonas aeruginosa (16.50%), Proteus spp. (13.40%), S. epidermidis (7.22%), E. coli (6.19%), S. saprophyticus (4.12%), and Klebsiella spp. (3.09%). Of the gram-negative isolated strains, only 18.75% (3/16) of the P. aeruginosa strains exhibited MBL production. A high prevalence rate was observed in the age-group 0–4 years (19.58%), followed by the age-groups, 5–9 and 15–19 (16.49% each), and the age-group >39 (10.31%). Levofloxacin, ciprofloxacin, amikacin, and fusidic acid were highly effective against the gram-positive, whereas ciprofloxacin, amikacin, and levofloxacin were potent against the gram-negative (except P. aeruginosa), while carbenicillin, meropenem and imipenem against the P. aeruginosa. The MBL-producers were highly (100%) resistant to IMP and MEM while highly (100%) sensitive to CAZ. In conclusion, the current study showed a high prevalence of S. aureus, P. aeruginosa, and MBL-producing P. aeruginosa (18.75%). Nevertheless, a high degree of resistance to antibiotics was noted, which could not be ignored. © 2024